The bamboo sawdust and addition of em4 as an alternative material for the cultivation of oyster mushroom (Pleurotus ostreatus). Issue 1 (October 2020) - Taskirawati, Ira; Baharuddin,; Pratiwi, F A
Abstract: Bamboo is a versatile and very close plant in people's daily lives in Indonesia. However, bamboo waste is a problem that usually arises in bamboo-based industries. The residues in question are in the form of leftover pieces of bamboo, and the powder from the processing process. Bamboo is an organic material with lignin, cellulose, and hemicellulose, where the bamboo content can use as a medium for growing oyster mushrooms. This study aimed to determine the growth of fungi by utilizing bamboo waste as the primary raw material using EM4 as a starter. The method used in this study is mixing raw materials (the cultivation media), sterilizing raw materials, inoculating, maintaining, and harvesting. There are four treatments also of EM4 as a starter, namely: without the addition of EM4 (P1) as a control; 1 ml EM4 (P2); 3 ml EM4 (P3); and 5 ml EM4 (P4) in 50 ml of water. Bamboo sawdust added 3 ml of EM4 (P3) when mixing media is the best media cultivation. This media cultivation takes 63 days from media cultivation inoculated by fungi until the oyster mushrooms are ready to be harvested.